TARI KEDURAI IMBANG SEMATO ALAM: REPRESENTASI BUDAYA BENGKULU - Venny Rosalina; Ediwar Ediwar (Institut Seni Indonesia Padang Panjang, 2014)
ABSTRAKKedurai Imbang Semato Alam merupakan sebuah wujud karya tari yang mengusung sebuah peristiwa budaya di Kabupaten Lebong. Kedurai Imbang Semato Alam merupakan inovasi baru yang berpijak dari upacara kedurai apem kemudian dilahirkan ke dalam bentuk koreografi tari. Kedurai apem berfungsi sebagai ritual tolak bala. Bebarapa hal yang terdapat dalam peristiwa budaya tersebut diantaranya nilai-nilai yang menjadi pokok mengenai upacara ini yang sangat erat hubungannya dengan masyarakat. Berkaitan dengan upacara ini bahwa ada hubung kait antara penjamuan kue (pesta kue) dengan bersih desa.Kata kunci: Karya Tari Kedurai Imbang Semato Alam, tolak bala, sistem budaya. ABSTRACTKedurai Imbang Semato Alam is represent a existing dance masterpiece carrying a cultural event in Regency Lebong. Kedurai Imbang Semato Alam is represent the new innovation which tread on from ceremony of kedurai apem then borne into dance choreography form. Kedurai Apem function as ritual refuse the army. Several things which is there are in the cultural event among other things values that becoming fundamental of concerning this ceremony is very hand in glove of its relation with the society. Correlate of this ceremony that there is linking barb between cake feast (cake party) with the countryside cleanness.Keys Word: Dance Masterpiece of Kedurai Imbang Semato Alam, refuse the army, cultural system.